Pengenalan Mobile Assisted Language Learning (MALL) untuk Berlatih Pronunciation - Tedi Rahmawati, Wiki; Harahap, Yunita Mutiara; Ginting, Rehdanana; Anggraini, Putri Redni; Maulana, Alpin Agus (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
This community service activity discusses the introduction of Mobile Assisted Language Learning (MALL) as an alternative media for practicing pronunciation, especially in learning English. MALL is a learning approach that utilizes mobile technology, such as smartphones, as a tool in the language learning process. The purpose of implementing this community service activity is to introduce how the use of MALL which assist to practice English pronunciation. This activity was carried out in the form of a small workshop to introduce several MALL applications that can be used to practice pronunciation. The participants in this activity were the students of English Education Study Program. The results of this activity indicate that the participants enthusiastically participated in the activity. Participants also demonstrated good skills when practicing the MALL application during the activity. Participants also had positive experiences in using MALL as a language learning tool. The introduction of MALL as a learning method can provide an effective media in improving participants' pronunciation skills. With the advancement of mobile technology that continues to grow, MALL has great potential to become an integral part of language teaching, especially English, in the future.